EFFECTS OF CORRUPT PRACTICES IN THE PUBLIC SECTOR: A CASE STUDY OF THE NIGERIAN POLICE SERVICE - Akamike, Joseph O.; Okonkwo, Osmond N.; Ojima, Davis (African Journal of Social and Behavioural Sciences, 2023)
This study empirically studied the repercussions of corrupt practices in the Nigeria public sector and the Nigerian police service as a case study. The study adopted the correlational survey methodology wherein, Corrupt Practices Questionnaire (CPQ) were developed and validated by the researchers. Data for the study were analysed using the Chi-square and Pearson correlation analytical procedures. Findings of the study revealed there is no relationship between gender and corruption in the Nigeria Police Service. Corrupt practices in the Nigeria Police Service are statistically dependent upon poor remuneration and conditions of service. There is also empirical evidence that corrupt practices persist in the service as a result of inadequate discipline and control in the rank and file of the service. The study therefore, recommended up-scale of discipline, control and better remuneration in the Nigerian Police Service. It further recommended that the officers should undergo periodic trainings to boost their competence, morale and level of commitment to service.